Etiology and risk factors of stroke in young adults: A multicentric study. (October 2022) - Aslam, Ayesha; Khan, Ubaid; Niazi, Farheen; Anwar, Iqra
Abstract: Objective: The main objective of this research was to assess the risk factors and causes of ischemic stroke in the young population (age less than 50 years). Methods: This was a prospective multicenter study conducted at Pakistan Atomic Energy Commission General Hospital, Islamabad, and Mayo hospital Lahore from June 2019 to June 2020. In this research, patients with ischemic stroke, aged 15–50 years were included. Prior to noting demographics, each patient gave ethical approval via filling out consent forms. After that, all demographical details including residence, education, gender and age, and socioeconomic status were noted. Risk factors were evaluated on the questionnaire proforma. Outcomes were measured using the modified Rankin scale (MRS) score. Additionally, data were analyzed by using SPSS V26. A P-value of <0.05 was set as statistically significant. Results: Out of 80 patients, 53 (66.25%) were male, while 27 (33.75%) were female. Six (7.5%) patients were between the ages of 15 and 25 years, 18 (22.5%) patients were between 26 and 35 years, 48 (60%) patients were between the ages of 36 and 45, and eight (10%) patients were between the ages of 46 and 50. According to this research, hypertension was found to be the most frequently occurring risk factor in 28 participants (35%), Diabetes mellitus in 23 patients (28.75%), dyslipidemia in 20 patients (22.5%), and smoking in 18 patients (22.5%). The etiology remained undetermined in 30 patients (37.5%). Most of the patients (87.5%) reported positive functional outcomes (MRS score 0–2). However, 3 (3.75%) patients died during the study period. Conclusion: This research showed that common risk factors of ischemic stroke in the local young population included hypertension, diabetes mellitus, and smoking, whereas the etiology of stroke remained unidentified in the majority of patients. Highlights: This study was conducted to evaluate causes and risk factors of ischemic stroke in young population (age less than 50 years). This was a prospective multicenter study conducted between June 2019 to June 2020. Patients with ischemic stroke, aged 15–50 years were included. Out of 80 patients, Hypertension was the most frequently found risk factor in 28 patients (35%), followed by Diabetes mellitus in 23 patients (28.75%), dyslipidemia in 20 patients (22.5%), and smoking in 18 patients (22.5%). The etiology remained undetermined in 30 patients (37.5%). This research showed that common risk factors of ischemic stroke in the local young population included hypertension, diabetes mellitus and smoking.